The clinical efficacy of auricular acupuncture in the treatment of frequent episodic tension-type headache: a single-blind randomized controlled trial - Xiaxia Jin; Ziwen Xu; Tao Gao; Gaofeng Wang; Wendi Dong; Junyi Jin; Yongmei Yan (BMC Complementary Medicine and Therapies)
Abstract Background Frequent episodic tension-type headache (FETTH) is a significant public-health concern. Scientific research has demonstrated that acupuncture can improve the clinical symptoms of FETTH. Purpose This study aimed to compare the efficacy and safety of auricular acupuncture and sham acupuncture in treating FETTH. Methods This was a randomized controlled trial. Participants with FETTH were randomly assigned in a 1:1 ratio to receive auricular acupuncture or sham acupuncture for 4 weeks, with follow-up lasting for up to 24 weeks. The primary outcomes were measured using the headache index and visual analog scale (VAS) score. Secondary outcomes included the Hamilton Anxiety Scale (HAMA) score, Hamilton Depression Scale (HAMD) score, blood flow velocity in the anterior cerebral artery (ACA), middle cerebral artery (MCA), and posterior cerebral artery (PCA) (VACA, VMCA, and VPCA, respectively), and the usage of acute headache medications. Adverse events were also recorded to assess safety. Results Compared with the sham acupuncture group, the auricular acupuncture group showed significant improvements in VAS score (2 (1.25, 2) vs. 3 (2, 3.5) at 24 h, P < 0.001; 2 (1.25, 2) vs. 2 (2, 3) at the 2nd week, P = 0.004; 2 (1, 2) vs. 2 (1.5, 3) at the 4th week, P = 0.015), headache index (4 (2, 7) vs. 7 (4, 9) at the 4th week, P = 0.016), HAMA score (11.69 ± 2.70) vs. (14.24 ± 3.20) at the 4th week, P < 0.001; (9.83 ± 2.71) vs. (11.95 ± 2.59) at the 8th week, P = 0.001; (9.67 ± 2.65) vs. (11.76 ± 3.00) at the 24th week, P = 0.002), HAMD score ((14.25 ± 2.68) vs. (15.89 ± 3.48) at the 4th week, P = 0.027,) VACA (85.5 (85, 86) vs. 83 (83, 84) at the 4th week, P < 0.001), VPCA (82 (81, 83) vs. 78 (77, 79) at the 4th week, P < 0.001), and usage of acute headache medications (8 (7, 10) vs. 9 (8, 11) at the 4th week, P = 0.030). The incidence of adverse events was similar between the two groups (P = 1.000). Conclusion This study found that auricular acupuncture effectively improved the clinical symptoms of FETTH and had relatively fewer side effects. Trial registration: The study was retrospectively registered in the International Traditional Medicine Clinical Trial Registry (ITMCTR2025000363) on January 20, 2025.